Fracture resistance and mode of failure of modified Polyether-ether-ketone versus lithium disilicate endocrowns - Mohamed G. A. Kharboush; Hesham I. Othman; Mohamed F. Aldamaty; Ahmed M. L. Alameldin (BMC Oral Health)
Abstract Purpose The current study aimed to compare modified Polyether-ether-ketone's fracture resistance and failure mode versus lithium disilicate glass–ceramic endocrowns. Materials and methods A total of 16 butt-joint endocrown specimens on mandibular second molar teeth were fabricated and divided into two equivalent groups; Pressable modified Polyether-ether-ketone (PEEK) (BioHPP®) and Pressable lithium disilicate glass ceramic (IPS e.max® Press). A computer-aided design/computer-aided manufacturing system was used to digitally create and milled wax patterns. Final restorations were cemented each to its corresponding prepared tooth. Thermomechanical cycling loading representing one year of clinical service was done in a chewing simulator. Fracture resistance was evaluated utilizing a universal testing machine. The failure mode was evaluated by inspecting fractured surfaces using a Stereomicroscope and further examined by a Scanning Electron Microscope (SEM) amongst both groups. Results A statistically significant variation in fracture resistance was recorded with a mean load of (2762.96 ± 216.15 N) for modified PEEK and (2175.91 ± 267.72 N) for lithium disilicate glass–ceramic endocrowns. Conclusion Modified PEEK endocrowns have higher fracture resistance than lithium disilicate glass–ceramic endocrowns. Moreover, the likeliness of catastrophic fracture in molars receiving endodontic treatment restored by modified PEEK is less than teeth restored with lithium disilicate glass ceramics.